Partial equilibrium mechanism and inter-sectoral coordination: An experiment - Nobuyuki Hanaki; Takashi Hayashi; Michele Lombardi; Kazuhito Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2021)
This study experimentally evaluates the performance of partial equilibrium mechanisms when different sectors run their mechanisms separately, despite the existence of complementarity between them. In our simple laboratory experiment setting that includes two sectors, each sector runs the top-trading-cycle mechanism. There is a Pareto-dominant equilibrium, but it requires coordination across sectors. Our results show that coordination failure occurs more frequently when there is asymmetry between the two sectors compared with the one-sector benchmark, even without inter-sectoral complementarity. When mechanisms are run sequentially across the two sectors, such failure is substantially reduced, compared with when they are run simultaneously.
Keywords: C92; D71; D82; 330; Partial equilibrium; inter-sectoral coordination; top-trading-cycle mechanism; laboratory experiment